FEATURES OF ECONOMIC DEVELOPMENT AND LIBERALIZATION - Saydirasulov Alisher Zokirovich; Komilov Feruz Qilichbek ugli (Scholar Express Journals, 2022)
Until now, in the chapter "priority directions of Economic Development and liberalization" of the strategy, it is necessary to protect the rights and guarantees of private property, to give full freedom to private entrepreneurship and small businesses, to prevent illegal interference of government agencies in their activities, to further expand the privatization of public property, to reduce the state participation in the charter, particular attention is paid to the issues of creating favorable conditions for the development of private entrepreneurship on the basis of privatized objects of public property, reducing the participation of the state in the socio-economic development processes of the country. In this article, information about the peculiarities of the development and liberalization of the economy is collected and comments are made.
Keywords: Sustainability; sectors of the economy; freedom; industry